2015
DOI: 10.1007/s11606-015-3438-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Hospital Admission of Non-critically Ill Patients Presenting to the Emergency Department: a Cross-sectional Study

Abstract: BACKGROUND:Little is known about the factors that influence physicians' admission decisions, especially among lower acuity patients. For the purpose of our study, non-medical refers to all of the factors-other than the patient's clinical condition-that could potentially influence admission decisions. OBJECTIVE: To describe the influence of non-medical factors on physicians' decisions to admit non-critically ill patients presenting to the ED. DESIGN: Cross-sectional study of hospital admissions at a single acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…Clinician behaviour in the ED context is addressed by a small number of studies from Canada and the USA. 17 18 Similarly, the operational and organisational features of an ED that may contribute to admission risk have been poorly studied, although there is some evidence that the 4-hour target—a policy introduced in England in 2004 to limit patients’ time in EDs to 4 hours—has led to a rise in short-stay admissions. 19 There is also evidence that levels of ED crowding increase rates of admission.…”
Section: Introductionmentioning
confidence: 99%
“…Clinician behaviour in the ED context is addressed by a small number of studies from Canada and the USA. 17 18 Similarly, the operational and organisational features of an ED that may contribute to admission risk have been poorly studied, although there is some evidence that the 4-hour target—a policy introduced in England in 2004 to limit patients’ time in EDs to 4 hours—has led to a rise in short-stay admissions. 19 There is also evidence that levels of ED crowding increase rates of admission.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-eight percent of hospitalists reported admitting patients even when the patient did not meet the admission criteria, consistent with previous research demonstrating the influence of factors other than clinical disease severity on triage decisions. 10 However, preventable admissions remain a hospital-level quality metric. 11,12 Triagists must often balance each patient's circumstances with the complexities of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic disease accounts for a considerable subset of ED visits and hospitalizations 26 , 27 and lack of access to primary care and outpatient specialty care are known contributors to increased ED use and hospitalizations. 28 , 29 Moreover, US patients with headaches and migraines seen in the ED account for substantial costs. 30 We previously observed that headache disorders accounted for one third of referrals to ICN.…”
Section: Discussionmentioning
confidence: 99%